Dissimilar Phonemes Create a Contextual Interference Effect During a Nonword Repetition Task - Meigh, Kimberly M.; Kee, Elisabeth (Frontiers in Psychology, 2020)
The contextual interference effect is a motor learning phenomenon where conditions that decrease overall learning during practice enhance overall learning with new tasks. Historically, practice conditions have elicited this effect in the limbs. In speech motor learning, these same conditions provide mixed results. Given that speech is a unique motor act influenced by language, we evaluated whether manipulating identical and similar phonemes (or sounds) induced contextual inference effects during speech motor learning. Using a cross-over design, participants with intact speech abilities underwent two nonword training protocols that varied by similar or dissimilar nonwords. The results suggested manipulating the similarity of phonemes within nonwords acted as interference variables during speech motor learning. Participants had greater speech accuracy when producing nonwords with similar phonemes during training and retention conditions. However, they produced significantly more speech errors when producing new similar nonwords during a transfer condition. Participants training with nonwords with different phonemes produced contrasting results: decreased accuracy during training and retention conditions but significantly higher accuracy when repeating new dissimilar nonwords during the transfer condition. These results suggest stimuli construction, specifically phoneme selection, may influence speech motor learning outcomes.